I Am What I Do—Negative Work as a Lens for the Study of Movement Chaplaincy - Wolff, Edda Stephanie (Religions, 2024)
This article explores the application of the concept of negative work within Movement Chaplaincy, contending that this framework facilitates engagement with negative spirituality in this sphere of ministry. Using the lens of the ‘work of the negative’, it examines the interplay between spirituality and political activism in Movement Chaplaincy, addressing potential resistance and inquiries surrounding the fusion of ‘negative spirituality’—focused on the apophatic and mystical-paradoxical aspects—and practical collective activism. This approach emphasizes the practical and theoretical aspects of challenging prevailing narratives, investigating self-subverting methods, and unearthing layers of non-identical elements within this process. It suggests that the evolving interest in the role of spirituality within social movements, coupled with initiatives like the Daring Compassion project, signifies a synergy between academic exploration and practical spiritual care provision. Ultimately, this article seeks to interpret activist work through the lens of spiritual accompaniment, creating space for an expanded understanding of activism across diverse identities and power dynamics. It proposes that the concept of ‘negative work’ serves as a tool for interpreting and deepening comprehension of the intrinsic dynamics within Movement Chaplaincy, fostering an inclusive and transformative approach to social and political change.